A formação do professor para o Ensino Superior de Administração - GUSMÃO, Silvia Souza (2015)
This study aimed to explore and describe how they form the teachers who work in the Administration of Higher Education in different locations in the Brazilian capital. To this end, we opted for a methodological approach Qualiquantitative nature using the Collective Subject Discourse method (DSC), based on the opinion of their own management professors. Thus, this study found, among other implications, the methods of learning and teacher training in administration are still based on traditional individual-cognitive logic of learning, which is based on explicit transmission and absorption of technical and professional knowledge; on teaching, pedagogy and teaching technologies; and the history and evolution of Directors. This form of knowledge transmission tends to transfer only a smaller portion of knowledge, the explicit dimension, is demonstrating thereby limited and reductionist, to leave the despised tacit dimension. It is therefore necessary to think of new methods of training that favor the tacit dimension of knowledge, based on the socio-practical perspective, exploring the possibilities of learning emerging from practical contexts and social structures of knowledge sharing, seeking to contribute to training full of this teacher.